2015
DOI: 10.1016/j.scr.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mesenchymal stromal cells through fine tuning of canonical Wnt signaling

Abstract: Mesenchymal stromal cells (MSCs) have been extensively utilized for various cell therapeutic trials, but the signals regulating their stromal function remain largely unclear. Here, we show that canonical Wnt signals distinctively regulate MSCs in a biphasic manner depending on signal intensity, i.e., MSCs exhibit proliferation and progenitor self-renewal under low Wnt/β-catenin signaling, whereas they exhibit enhanced osteogenic differentiation with priming to osteoblast-like lineages under high Wnt/β-catenin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…Similarly, we recently showed that fine tuning the mesenchymal niche is critical for regulating the regenerative activity of HSCs [19] and that functional alterations of MSCs are related to heterogeneous clinical prognosis in hematological malignancies[20]. The niche activity of MSCs can thus exert a significant impact on the regenerative activity of HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we recently showed that fine tuning the mesenchymal niche is critical for regulating the regenerative activity of HSCs [19] and that functional alterations of MSCs are related to heterogeneous clinical prognosis in hematological malignancies[20]. The niche activity of MSCs can thus exert a significant impact on the regenerative activity of HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[78] Adipo-to-osteo transdifferentiation Wnt/b-catenin signalling is a master regulator of adipocyte and osteoblast maturation whereby an accumulation of bcatenin was observed to cause a dose-dependent increase in osteogenesis and a dose-dependent decrease in adipocyte differentiation. [79,80] For instance, b-catenin knockout within the preosteoblasts of mice resulted in an increase in bone marrow adiposity and a decreased bone mass. [83] Wnt-3a is documented to be an inducer of Wnt signalling so that culturing mouse BMSC-derived preadipocyte and preosteoblast cells in a Wnt-3a conditioned medium led to the induction of the Wnt pathway and upregulation of the TCF/LEF gene within preosteoblasts.…”
Section: Signalling Pathways In Osteoblastogenesismentioning
confidence: 99%
“…[83] In addition, MSCs demonstrating b-catenin expression were associated with bone mineralisation, an upregulated ALP expression and a downregulation of aP2 and PPARc expression. [79] Furthermore, b-catenin acts as a transactivation molecule depending on the levels accumulated within MSCs. [79] Low b-catenin levels result in the expression of genes responsible for cell cycle regulation whilst high b-catenin levels are associated with the expression of genes responsible for pathway signalling like that in osteoblast maturation.…”
Section: Signalling Pathways In Osteoblastogenesismentioning
confidence: 99%
See 2 more Smart Citations